An empirical study from Chinese energy firms on the relationship between executive compensation and corporate performance - Han, Li; Yu, Han-Hsing (Nurture, 2023)
Purpose: This study investigates the relationship between executive compensation and firm performance in Chinese new energy companies. Design/Methodology/Approach: The financial data of 122 Chinese-listed energy companies from 2010-2021 is selected for the empirical study. Findings: Executives’ monetary compensation and executives’ shareholding ratio are positively related to corporate performance. Overseas background and financial background play a moderating role in the effect of executives’ monetary compensation and their shareholding ratio on corporate performance. Conclusion: The fact that executives’ salaries and shareholding both have a significant positive impact on business performance demonstrates the effectiveness of pay incentives and equity-based incentive. The research additionally demonstrates that an executive’s financial knowledge and experience in other countries alter the impact of cash and equity pay on company performance. Research Limitations/Implications: The research excludes a large number of key energy businesses, especially rising ones in the clean energy sector, as it solely targets publicly traded businesses for ease of data collection. Practical Implications: The survey results help to further understand the key factors of compensation incentives for managers in energy companies and are informative for the effectiveness of compensation incentives in energy companies. Contribution to Literature: This study provides empirical results on the impact of managerial compensation on firm performance in energy firms in the Chinese context, adding a new step to the existing literature.